COMMUNITY DEVELOPMENT ACTIVITIES THROUGH KKN TEMATIK FAMILY EMPOWERMENT POS (POSDAYA) - Pratidina, Ginung (Universitas Djuanda, 2015)
Posdaya Thematic Field Work Experience (KKN) is part of the learning activities undertaken by the students that aims to help empower people with emphasis on four aspects, namely education, health, environment, and the local economy. Through the program, the students may improve the quality of the family in building theirselves into a prosperous family, independent families, and families are able to face the challenges of the future better. As many as 160 students from seven faculties of Bogor Djuanda University the Posdaya Thematic KKN followed and implemented in District Ciawi and Megamendung for forty days, from 12 August to 20 September 2014. During this period, the students managed to establish 15 Posdaya and implement programs that include Education by providing tutoring, educational seminars, provision of libraries and the establishment of early childhood education. Health Sector perform Saturday Clean Program, Helping IHC Activity, Healthy Way, cultivation of Medicinal Plants. Economics training manufacture of food products, crafts, seminars manufacture Household Industrial Permit (IRT) and halal certification from MUI. Environmental Affairs held Agricultural Extension and Waste Management. Achievement of targets and outcomes of nearly 100 percent with the main obstacle is the lack of capital and lack of synergy between the public, private and local government.